Pengaruh Model Inquiry Training dan Berpikir Kritis Terhadap Kemampuan Berpikir Ilmiah Mahasiswa pada Mata Kuliah Kimia Dasar - Rita Syafitri; Rayandra Asyhar; Asrial Asrial (Universitas Jambi, 2016)
This study was based on less varied learning model used in chemistry and to practice thinking skills that students can apply the concepts to solve chemical problems. It was done to try out the inquiry training model. The research instruments were used to measure dependent variable which is scientific thinking. Two learning models were applied: inquiry training model applied on the experiment group and lecture method applied on the control group. Critical thinking as the moderator variable that was measured through the critical thinking tests. The experimental research used 2 x 2 factorial design 8 meeting. The data were analyzed using two ways Anova and Tuckey test. The study concluded that: 1) There are differences of the scientific thinking skills between the inquiry training model and the lecture method learning model. 2) There is a significant difference of the scientific thinking skills between low and high level of critical thinking skills. 3) There are differences of scientific thinking skills of low levels critical thinking students between students who were taught by inquiry training model and that of by lecture learning method. 4) There are differences in scientific thinking skills among the group of students who had high level of critical thinking taught by inquiry training model and lecturing learning model. 5) There is no interaction between the application of inquiry training model to the level of critical thinking to the students scientific thinking skills.